A Review of Chalcogenide Thin Films for Solar Cell Applications - Ho, Soon Min; Anand, T. Joseph Sahaya (Informatics Publishing Limited, 2015)
In this work, authors review the current state of research in chalcogenide thin films in order to study the use of films for the fabrication of cost-effective solar cells. As far as we know, various techniques have been employed to prepare thin films such as electro deposition, chemical bath deposition, flash evaporation, spray pyrolysis, successive ionic layer adsorption and reaction and so on. The obtained films showed that the band gap values are ranged from one to two eV which match to solar spectrum.